A Homestay Development Based On Traditional Architecture And Ethno Design Of Toba Traditional Houses With The Marga Kinalsystem In Lumban Suhi-Suhi, Pangururan District, Samosir Regency - Rytha Tambunan; Fotarisman Zaluchu (INFOKUM, 2025)
Community service program that focuses on improving the welfare and economy of the community, Lumban Suhi-Suhi Village, Pangururan District, Samosir regency. This program was implemented from may 2024 and ended in December 2024. Using the fo-cus group discussion (FGD) method with homestay owners to provide training for own-ers/family clans on managing the Batak Toba traditional house homestay in improving the community's economy and maintaining cultural heritage products by maintaining the uniqueness of traditional architecture and ethno design of the Batak Toba house. The re-search methods include field studies, in-depth interviews with local indigenous commu-nities, and a literature review of Toba traditional architecture. This approach explores cul-tural elements applicable to homestay designs, such as building structures, traditional ornaments, and spatial layouts that reflect the lifestyle of the Batak Toba community. The Batak Toba traditional house has a high cultural value, especially in terms of aesthetics and as a cultural heritage product that really needs to be maintained. The Batak tradi-tional house that is still being empowered must continue to be preserved to maintain the culture it has. One of the most effective ways to empower the Batak Toba traditional house into a homestay. So that the development of this kinship-based homestay willpro-vide welfare for the family and clan owners.